2007
DOI: 10.1128/jvi.00571-07
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Papillomavirus Type 1 Infection Is Mediated by SNARE Syntaxin 18

Abstract: Events that lead to viral infections include the binding of the virus to the target cells, internalization of the virus into the cells, and the ability of the viral genome to be expressed. These steps are mediated by cellular and viral proteins and are temporally regulated. The papillomavirus capsid consists of two virally encoded capsid proteins, L1 and L2. Much is known about the role of the major capsid protein L1 compared to what is known of the role of the L2 protein. We identified the interaction of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
35
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 51 publications
2
35
0
Order By: Relevance
“…Using polyomavirus-like particles encapsidating reporter DNA, investigators previously found two pathways for viral trafficking, one leading to the efficient delivery of the pseudogenome and the other along a noninfectious route (21). Our laboratory has described the internalization and trafficking of noninfectious mutant PsVs, which appear to traffic identically to wild-type (WT) PsVs until about 4 h postinternalization, when the WT virions arrive at the syntaxin 18-positive region of the cell and the mutant virions appear to be retained in the lysosomes (22). Indeed, it has been shown that for roughly every 2,000 wartderived BPV1 virions, only 1 viral particle is infectious (33).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Using polyomavirus-like particles encapsidating reporter DNA, investigators previously found two pathways for viral trafficking, one leading to the efficient delivery of the pseudogenome and the other along a noninfectious route (21). Our laboratory has described the internalization and trafficking of noninfectious mutant PsVs, which appear to traffic identically to wild-type (WT) PsVs until about 4 h postinternalization, when the WT virions arrive at the syntaxin 18-positive region of the cell and the mutant virions appear to be retained in the lysosomes (22). Indeed, it has been shown that for roughly every 2,000 wartderived BPV1 virions, only 1 viral particle is infectious (33).…”
mentioning
confidence: 99%
“…Our laboratory identified BPV1 pseudovirions (PsVs) in the ER using transmission electron microscopy, and immunofluorescence studies showed colocalization between BPV1 and the ER marker calnexin (4,22). We characterized the interaction between the ER-resident protein syntaxin 18 and the BPV1 minor capsid protein L2, an interaction necessary for infection (22).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…33 On the other hand, it has been proposed that HPV 16 initially enters via clatrin-coated pits but the traffic occurs through caveosomes to eventually reach the endoplasmic reticulum. 51,52 Moreover, it has been suggested that the capsids might be internalized via a novel pathway involving tetraspanin-enriched microdomains. 53 The uncoating is not observed until 8-12 hours after cellsurface binding, and it seems that L2 plays a critical role in the endosome escape.…”
Section: Natural History Of Hpv Infectionmentioning
confidence: 99%
“…Spliced viral mRNA was first detected at 12 hours postinfection, and in most assay systems infection is not robustly detected until at least 24 hours after capsid binding. 46,51 The pathway involved in internalization and intracellular trafficking is still unclear, but it seems to occur slowly and asynchronously over a span of several hours. 50 Clathrin-mediated endocytosis has been pointed out to be like the endocytotic pathway for the majority of HPV types.…”
Section: Natural History Of Hpv Infectionmentioning
confidence: 99%